Effectiveness of Social Science Learning on Socialization of Earthquake Disaster Potential and its Mitigation to Students of Junior High Schools in the City of Bandung - Arnie Fajar; Ernandia Pandikar; Dachlan Rahadian (LPPM Universitas Pendidikan Mandalika, 2022)
This study aims to analyze the level of effectiveness of social studies learning on the socialization of potential earthquake disasters in the Bandung City Region and its mitigation in Junior High School (SMP) students in Bandung City. The approach used in this study is a quantitative approach, while the method used is descriptive analysis with a survey type with a sample of 194 people determined by proportional random sampling from 3931 students who are in areas prone to earthquakes in the city of Bandung, contained in 14 public junior high schools. The instruments used are observation, questionnaires, and documentation studies. The data analysis technique used descriptive statistics and inferential statistics. Based on the results of the study, it was shown that the effectiveness of social studies learning on the socialization of potential earthquake disasters in the city of Bandung along with its mitigation to the students of public junior high schools in the city of Bandung showed a positive and significant correlation, which had a relationship level of 67.8% with a correlation coefficient value of  0.824 which is included in the category of very strong relationship. The social studies curriculum for junior high schools made a fairly high contribution to disaster education and disaster mitigation, which was 47.4% in the social studies curriculum for junior high schools based on Permendiknas no. 22 of 2006, and 69.2% of the social studies curriculum for junior high schools based on Permendikbud No. 24  of 2016.